2019
DOI: 10.1111/jppi.12283
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Health of Caregivers of Children Who Have an Intellectual/Developmental Disability

Abstract: There are a growing number of children with an ID/developmental disability. As well, there is evidence of poor health in the caregivers of these children. This article describes a narrative review of the literature regarding the mental and physical health of caregivers of children with ID/developmental disability. The review examined 162 papers. Twenty‐three different factors were identified that may have an effect on the health of these caregivers. Social determinants, individual caregiver variables, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 164 publications
0
24
0
Order By: Relevance
“…Inconsistent differences between mothers and fathers of children with developmental disabilities have been identified in relation to their health (Davis & Carter, 2008;Marquis, Hayes, & McGrail, 2019), parental roles (Glidden & Natcher, 2009;Hartley, Barker, Seltzer, Greenberg, & Floyd, 2011), perceptions and attitudes (Simmerman, Blacher, & Baker, 2001), and markers of chronic stress (Foody, James, & Leader, 2015). Mothers have been shown to have poorer mental health (Davis & Carter, 2008;Emerson & Llewellyn, 2008;Foody et al, 2015) and lower levels of well-being (Olsson & Hwang, 2008) than fathers.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent differences between mothers and fathers of children with developmental disabilities have been identified in relation to their health (Davis & Carter, 2008;Marquis, Hayes, & McGrail, 2019), parental roles (Glidden & Natcher, 2009;Hartley, Barker, Seltzer, Greenberg, & Floyd, 2011), perceptions and attitudes (Simmerman, Blacher, & Baker, 2001), and markers of chronic stress (Foody, James, & Leader, 2015). Mothers have been shown to have poorer mental health (Davis & Carter, 2008;Emerson & Llewellyn, 2008;Foody et al, 2015) and lower levels of well-being (Olsson & Hwang, 2008) than fathers.…”
Section: Background and Significancementioning
confidence: 99%
“…Fathers were also found to have higher stress (Rivard, Terroux, Parent-Boursier, & Mercier, 2014) and more negative indicators of physiological health (increased heart rate variability and higher blood pressure) than mothers (Foody et al, 2015). Few studies have compared health, stress, or parenting among fathers and mothers of children with ID within the AYA developmental period (Marquis et al, 2019;Patton et al, 2018).…”
Section: Background and Significancementioning
confidence: 99%
“…There is a considerable amount of literature regarding the effects of having a child with a developmental disability (DD) on the mental health of parents (see Marquis et al for a review1). Studies have found both an increase in mental health problems among these parents2–4 and no difference in mental health between parents of children with a DD and parents of children without a DD 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical frameworks such as family systems theory recognise that fathers are an integral part of the family unit (Seligman and Darling, ). The birth and care of a child with an intellectual disability (ID) is understood to affect every member of the family, including fathers, yet few studies have explored fathers' well‐being (Braunstein et al, ; Macdonald and Hastings, ; Marquis et al, ; Taylor et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Other more distal environmental factors may also put fathers at risk of poorer outcomes, with one of the most significant being income poverty (Marquis et al, ). The developmental systems model postulates that living in poverty and low levels of parental education are factors associated with ‘non‐optimal' levels of child development (Guralnick, ).…”
Section: Introductionmentioning
confidence: 99%